Comparing optical coherence tomography radial and cube scan patterns for measuring Bruch's membrane opening minimum rim width (BMO-MRW) in glaucoma and healthy eyes: cross-sectional and longitudinal analysis. Issue 3 (3rd August 2017) - Kabbara, Sami W; Zangwill, Linda M; Mundae, Rusdeep; Hammel, Naama; Bowd, Christopher; Medeiros, Felipe A; Weinreb, Robert N; Belghith, Akram
Abstract : Aim: To compare the cube and radial scan patterns of the spectral domain optical coherence tomography (SD-OCT) for quantifying the Bruch's membrane opening minimum rim width (BMO-MRW). Methods: Sixty healthy eyes and 189 glaucomatous eyes were included. The optic nerve head cube and radial pattern scans were acquired using Spectralis SD-OCT. BMO-MRWs were automatically delineated using the San Diego Automated Layer Segmentation Algorithm. The BMO-MRW diagnostic accuracy for glaucoma detection and rates of change derived from the two scan patterns were compared. Results: There was a significant difference between the baseline global BMO-MRW measurements of cube and radial scans for healthy (301.9±57.8 µm and 334.7±61.8 µm, respectively, p<0.003) and glaucoma eyes (181.2±63.0 µm and 210.2±67.2 µm, respectively, p<0.001). The area under the receiver operating characteristic curve for differentiating between healthy and glaucoma eyes was 0.90 for both the radial scan-based and cube scan-based BMO-MRW. No significant difference in the rate of BMO-MRW change (mean follow-up years) by scan pattern was found among both healthy (cube: −1.47 µm/year, radial: −1.53 µm/year; p=0.48) (1.6 years) and glaucoma eyes (cube: −2.37 µm/year, radial: −2.28 µm/year; p=0.45) (2.6 years). Conclusion: Although the cube scan-based BMO-MRW was significantly smaller than the radial scan-based BMO-MRW, we found no significant difference between the two scan patterns for detecting glaucoma, identifying BMO location and measuring the rate of BMO-MRW change. These results suggest that although BMO-MRW estimates are not interchangeable, both scan patterns can be used for monitoring BMO-MRW changes over time.